2014
DOI: 10.1002/pat.3440
|View full text |Cite
|
Sign up to set email alerts
|

Liquid oxygen compatibility and thermal stability of bisphenol A and bisphenol F epoxy resins modified by DOPO

Abstract: Bisphenol A and bisphenol F epoxy resins (BA and BF) were chemically modified by 9,10‐Dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide to improve their liquid oxygen compatibility. The structures of the modified epoxy resins were confirmed by Fourier transform infrared spectroscopy. Significant enhancement of liquid oxygen compatibility for the modified resins was detected according to the liquid oxygen mechanical impact test. Thermogravimetric analysis showed that during the degradation in oxygen atmosphere, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Reduction in combustibility of the epoxy resins by using phosphorus‐containing retardants has become a pivotal part of the development and application especially in aerospace industries and electrical/electronic fields . Among these phosphorus‐containing retardants, 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) derivatives are attractive because of their relatively high thermal stability and flame‐retarding efficiency. Furthermore, phosphorus‐containing reactive imine can be used as curing agent and flame retardant in epoxy resins .…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in combustibility of the epoxy resins by using phosphorus‐containing retardants has become a pivotal part of the development and application especially in aerospace industries and electrical/electronic fields . Among these phosphorus‐containing retardants, 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) derivatives are attractive because of their relatively high thermal stability and flame‐retarding efficiency. Furthermore, phosphorus‐containing reactive imine can be used as curing agent and flame retardant in epoxy resins .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that DOPO-modified bisphenol A epoxy resin was compatible with liquid oxygen at 2 wt% phosphorus content. 25 Therefore, the differences among the liquid oxygen compatibility of the modified resin system were that the IRS could be further lowered by reducing the SR value. This could be attributed to the reduced rigidity by decreasing the SR value in the resin at cryogenic temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, phosphorus‐containing compounds have shown extensive application as halogen‐free flame retardants in epoxy resin . 9,10‐Dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) is a type of cyclic phosphate with a diphenyl structure, which can react with epoxy monomer . As reported in previous studies, DOPO and its derivatives can significantly improve the flame retardancy of epoxy resin.…”
Section: Introductionmentioning
confidence: 91%